The Delta Survey Workshop : Proceedings from Conferences held in Alexandria (2017) and Mansoura (2019) - Wahby, Ayman (Archaeopress Publishing, 2022)
The Delta Survey Workshop comprises the proceedings of two conferences organised by the Delta Survey Project and held in Alexandria in 2017 and Mansoura in 2019. The 23 papers contain the results of the latest fieldwork in the Nile Delta and Sinai, from survey work that records and documents unknown and new sites such as Kom Dabaa and Mutubis or sites in Kafr Dawar and Wadi Tumilat, to excavation reports from established projects at major sites such as Qantir, Bubastis, Tell Heboua, Tell el-Maskhuta, Akademia, Taposiris Magna and Tell Fara'in (Buto). New work is also reported from Tell Tebilla, urban funerary sites in Alexandria, and Arab el Hisn (Heliopolis). There are also thematically focussed papers covering ovens recorded in archaeological and ethnological fieldwork, tower houses, amphorae and pottery and human remains. In addition, there are mapping and remote sensing reports from Mariut and the Buto area, rock inscriptions in Sinai and a catalogue project of material in the St Mark antiquities collection in Alexandria.